Russian expansion towards Persia until 1556-1907 AD - Lectu. Hassan Ghanem Abed Radan (Journal of College of Education, 2026)
Russia aspired to join the ranks of the most active and economically and militarily developed European countries. Due to the harsh nature of Russia's geographical location, it strove to break free of the constraints of nature by opening up horizons that would enable it to access warmer waters, which would contribute to raising its status both internally and externally. Therefore, the Russian tsars sought to break the isolation that Russia had experienced for centuries from Europe by gaining access to seas open to navigation throughout the year and searching for ports that would help them export in warm waters. Despite Russia's control over a number of seas, including the Baltic and Caspian Seas, these seas were of no real benefit to Russia. The Baltic Sea is frozen for most months of the year, and the Caspian Sea is an inland sea. This prompted Russia to turn its attention to Persia, given its location in southern Russia and its long borders with it, and because Persia possessed a number of important ports overlooking the eastern coast of the Arabian Gulf. Russia therefore sought to expand its trade with Persia. Focusing on Persia, this study highlights the importance of shedding light on the nature of the historical events, both economically and militarily, that accompanied Russian expansion and demonstrating the extent of its impact on both the Russian and Persian sides, despite the long historical period covered by this study.
Keywords: Russian expansion into Persia, Russia's position on internal developments in Persia